Analisis Perbandingan Kadar Glukosa Beras Berdasarkan Cara Memasak: Comparative Analysis of Rice Glucose Levels Based on Cooking Methods - Lidia Kabangnga'; Eka Farpina; Askur (Jurnal Agritechno, 2026)
Rice is the main staple food source in Indonesia with an annual consumption of 25.3 million metric tons. The processing method of rice into cooked rice can affect the glucose levels produced, which is important for diabetes mellitus patients. This study aims to compare the glucose levels of white rice, red rice, and black rice based on cooking methods using a rice cooker and a steamer. The research method used was quasi-experiment. The samples consisted of three types of rice (white, red, and black) cooked using a rice cooker and a steamer. The percentage reduction in glucose levels was measured using the Luff Schoorl method according to SNI 01-2891-1992 standards with three repetitions for each sample. Data analysis was performed using One Way Anova followed by Tukey’s post hoc test. The results showed that the percentage reduction of glucose levels in rice cooked by rice cooker was lowest in white rice (16.5213%), followed by red rice (23.4100%), and highest in black rice (28.7544%). For the steamer cooking method, the glucose reduction percentage was lowest in white rice (21.7523%), red rice (27.5385%), and highest in black rice (33.7945%). Statistical data showed a significant difference in glucose levels among the groups with a significance value of 0.000 < 0.05. The study concludes that there is a significant difference in glucose levels between white, red, and black rice based on the cooking method used, rice cooker or steamer. The results also indicate that the glucose levels in rice cooked by steamer are lower compared to rice cooked by rice cooker, and among the three rice types, black rice has the lowest glucose level, followed by red rice and white rice.